Social lives and cliques within senior housing communities. Issue 3 (2nd September 2019) - Ewen, Heidi H.; Dassel, Kara B.; Chahal, Jasleen K.; Roberts, Amy R.; Azugbene, Ehiremen
ABSTRACT: A better understanding of social environments will benefit facilitation of social cultures within senior housing communities. Social cliques naturally form among groups of people, particularly those living in close proximity. Research has shown that often older adults experience stigma based upon their health status and are excluded from social groups. This study examined residents' perceptions of life in senior housing, social stigma, and cliques. Forty-eight residents from two types of senior housing communities participated in the study. Qualitative thematic coding was used to analyze responses to open-ended interview questions. Overall, residents reported satisfaction with the community and their privacy and reported difficulties with distance from family, caregiving, and bereavement. The majority were able to identify cliques, defining them based upon common interests, health status, and shared histories. The most salient finding was that while social cliques existed they were not a source of dissatisfaction or stigma.